Brain-Language Research: Where is the Progress? - Friedemann Pulvermüller (Biolinguistics, 2010)
Recent cognitive neuroscience research improved our understanding of where, when, how, and why language circuits emerge and activate in the human brain. Where: Regions crucial for very specific linguistic processes were delineated; phonetic features and fine semantic categories could be mapped onto specific sets of cortical areas. When: Brain correlates of phonological, syntactic and semantic processes were documented early-on, suggesting language understanding in an instant (within 250ms). How: New mechanistic network models mimicking structure and function of left-perisylvian language areas suggest that multimodal action-perception circuits — rather than separate modules for action and perception — carry the processing resources for language use and understanding. Why language circuits emerge in specific areas, become active at specific early time points and are connected in specific ways is best addressed in light of neuroscience principles governing neuronal activation, correlation learning, and, critical-ly, partly predetermined structural information wired into connections between cortical neurons and areas.